Kepentingan Pengetahuan Sedia Ada Dalam Bacaan Dan Pemahaman : Satu Sorotan Ringkas - Mohamed, Shukery; Abdullah, Zaharah (Penerbit Universiti Sains Malaysia, 1998)
This article discusses the importance of reading in language education. In order to teach reading effectively, there are various factors that should be taken into consideration. Based on research findings, one of the most important factors which contributes to a high level of reading comprehension is 'background knowledge'. The review of literature on 'background knowledge' in this article could help bring about awareness and create interest among teachers teaching reading and help them to explore the subject in a more academic and scientific manner.